1975
DOI: 10.1128/aem.30.2.319-323.1975
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Clostridium botulinum by Strains of Clostridium perfringens Isolated from Soil

Abstract: Thirty-one soil samples were examined for the presence of organisms capable of inhibiting growth and toxin production of strains of Clostridium botulinum type A. Such organisms were found in eight samples of soil. Inhibiting strains of C. perfringens were found in five samples, of C. sporogenes in three and of Bacillus cereus in three. Three of the C. perfringens strains produced an inhibitor effective on all 11 strains of C. botulinum type A against which they were tested, seven of eight proteolytic type B st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 8 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…The detection of C. botiuliniin in soil may be inversely related to the occurrence of organisms that inhibit its growth. Some strains of C. perfringens and C. sporogenies from soil are inhibitory for type A, B, C, and F strains of C. botiuliniin, but inhibition was not described for type D strains (15). However, C. botildiniun type D organisms and neurotoxin were identified in necropsy specimens collected from three human cadavers in this area (22).…”
Section: Resultsmentioning
confidence: 90%
“…The detection of C. botiuliniin in soil may be inversely related to the occurrence of organisms that inhibit its growth. Some strains of C. perfringens and C. sporogenies from soil are inhibitory for type A, B, C, and F strains of C. botiuliniin, but inhibition was not described for type D strains (15). However, C. botildiniun type D organisms and neurotoxin were identified in necropsy specimens collected from three human cadavers in this area (22).…”
Section: Resultsmentioning
confidence: 90%
“…This may just be due to variations in soil pH rather than organic content, although Böhnel & Lube (2008) postulate that the general lack of microporous aeration, or raised nutrient contents in decaying organic matter, may assist in triggering C. botulinum growth. Smith (1975b) identified a statistically significant relationship between higher counts of C. botulinum types A and B in neutral to alkaline soils. However, in a later study, Smith (1978) found a higher prevalence of C. botulinum type A in neutral-alkaline soils (average pH 7.5), whereas type B prevailed in slightly more acidic soils (average pH 6.25).…”
Section: Soil Chemistrymentioning
confidence: 89%
“…The introduced C. botulinum spores had to compete with the indigenous microbial community of the soil and compost. Especially C. perfringens which has similar requirements to the microenvironment as C. botulinum is known to inhibit the growth and toxin production of C. botulinum in co‐cultures (Smith, 1975; Sandler et al ., 1998; Monge‐Izaguirre & Rodriguez‐Cavallini, 1999). In our study, however, the development of the C. perfringens and the C. botulinum populations in the soil were positively correlated, an inhibitory effect could not be seen.…”
Section: Discussionmentioning
confidence: 99%